Analisis Pemanfaatan Exhaust Fan Skala Rumah Terhadap Kinerja Turbin Angin Tipe Savonius Sumbu Vertikal - Dharmawan, Quewys Alqorni Mada; Anwar, Choirul; Jatira, Jatira; Abdulah, Amri (Jurnal Teknologika, 2025)
The fossil fuel crisis in Indonesia, which contributes 85% of the national energy mix, has driven the need to utilize renewable energy sources, one of which is exhaust wind as industrial waste energy that has high speed (5-7 m/s) and good flow continuity. This study developed a vertical Savonius turbine with variations in exhaust-turbine distance (20, 30, 40 cm) and measured wind speed (5.3, 6, 6.4 m/s) to optimize the utilization of this energy. The results showed that the 20 cm configuration produced the best performance with a maximum power of 5.98 watts at a speed of 6.4 m/s and a Coefficient Performance (CP) of 0.16, which is 31% more efficient than a distance of 40 cm, proving the potential of exhaust wind as a renewable energy solution that is applicable in industry with a payback period of less than 3 years and the potential for reducing the load on the electricity network by up to 15%.